Application of Problem Based Learning Models To Improve The Innovative Ability Of Basic School Students - Setiawan, Wawan; Sa'ud, Udin Saefudin; Sujana, Atep; Sopandi, Wahyu (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The purpose of this study is to apply a problem based learning model based on improving the ability to think innovations carried out on the Role of Economics. Thus increasing the ability of innovative thinking skills is very important to determine decisions in solving learning problems. In improving the innovative thinking ability of elementary school students, it is used in the Problem Based Lerning model on the economic role material. So that the research method used is the experimental method with the design of The One-Group PretestPostest Design. The research population is the fifth grade students at SDN leuwihieum, Jatigede Subdistrict, Sumedang Regency. The instrument used consists of test instruments, namely the Innovative Thinking Skills Test, which aims to find out the improvement of innovative thinking skills and non-test instruments in the form of observation formats, student daily journals and field notes. The importance of research in learning Problem Based Lerning models significantly increases Innovative thinking skills while research directs that Primary School teachers can use continuously and continuously in learning Probelem Based Lerning models so that their use for Primary School students continues to increase and adds to effective and efficient learning